Phylogeny of Amorphophallus (Araceae) on Borneo with notes on the floral biology of three species - Wong, Sin Yeng; Nor Fathiah, Abd Rahim; Hetterscheid, Wilbert L.A. (National Taiwan University, 2022)
This study was undertaken on Amorphophallus of Borneo to address two questions: (1) to determine the phylogenetic relations among taxa of Bornean Amorphophallus and (2) to investigate the floral biology and floral visitors of three Amorphophallus species. Phylogenetic analyses were carried out by using one plastid region: matK, and two nuclear regions: ITS and PhyC, with a total of 98 accessions representing 56 taxa of Amorphophallus. Floral biology of three Amorphophallus species (A. hewittii, A. eburneus, and A. julaihii) were investigated. Bornean Amorphophallus is separated into three groups within subgen. Amorphophallus: A. angulatus and A. pendulus of the Paeoniifolius-Manta clade, A. ranchanensis as sister taxon to clade A, clade Pusillus II, and clade B. The anthesis of A. hewittii and A. eburneus lasted for ca. 49 hours and ca. 64 hours respectively. The pistillate anthesis was much longer in A. hewitti (36 hours) than A. eburneus (24 hours) but the staminate anthesis was much shorter in A. hewittii (13 hours) than A. eburneus (40 hours). Floral visitors to A. hewittii are different to those visiting A. eburneus and A. julaihii; the latter two species attract less visitors and belong to clade A where hitherto no species has been investigated.